Mudanças de regimes na função de reação do Banco Central do Brasil: uma abordagem utilizando markov regime switching - Rodrigues, Wellington Gonçalves (2015)
The goal of this paper is to identify the occurrence, duration and transition probabilities of different monetary policy regimes in Brazil since the implementation of the inflation-targeting regime in 1999. To estimate the reaction function of the Central Bank of Brazil, a forward looking Taylor Rule for an open economy is adopted and a Markov Regime Switching methodology applied in order to allow for endogenous regime switches in monetary policy. The results indicate the presence of three distinct monetary policy regimes since the implementation of the inflation-targeting regime in Brazil. The first regime occurs during 21% of the studied period and is characterized by a discretionary approach not following the Taylor Rule and a stronger focus in the reaction to the output gap. A balance in the weights given to the output gap and inflation expectations deviation from target and the adherence to the Taylor Rule characterizes the second regime, which is present in 67% of the time. The third regime is characterized not only by its adherence to the Taylor Rule but also by a stronger focus in the reaction to the deviation of inflation expectations from the target, being present in 12% of time.